Select the point that satisfies the equation
![Select the point that satisfies the equation class=](https://us-static.z-dn.net/files/d38/3f936e5a330588ef04973fde58579c55.png)
Answer:
option C
(4,4)
Step-by-step explanation:
Given in the question an inequality
y ≤ x² - 3x + 2
(1,1)
when x = 1
y ≤ 1² - 3 + 2
y ≤ 0
1 ≤ 0
Rejected as 1 is greater than 0
(2,2)
when x = 2
y ≤ 2² - 3(2) + 2
y ≤ 0
2 ≤ 0
Rejected as 2 is grater than 0
(4,4)
when x = 4
y ≤ 4² - 3(4) + 2
y ≤ 6
4 ≤ 6
Accepted as 4 is lesser than 6
(3,3)
when x = 3
y ≤ 3² - 3(3) + 2
y ≤ 2
3 ≤ 2
Rejected as 3 is greater than 2
Answer:
The correct answer is option A (5, 5)
Step-by-step explanation:
From the figure we can see an equation
y ≤ x² - 4x + 2
Check option A (5, 5)
Substitute the value of x and y in equation
y ≤ x² - 4x + 2
5 ≤ 5² - (4 * 5) + 2
5 ≤ 25 - 20 + 2
5 ≤ 27 - 20
5 ≤ 7
It is true. Therefore the first option is the correct answer